The Rhyacophila fasciata Group in Europe: Rhyacophila macedonica Karaouzas, Valladolid & Ibrahimi (n. sp.) from Greece, Kosovo, Republic of North Macedonia and Serbia (Trichoptera: Rhyacophilidae) - Valladolid, Maria; Karaouzas, Ioannis; Ibrahimi, Halil; Arauzo, Mercedes; Stamenković, Valentina Slavevska; Dorda, Beatriz A.; Hinić, Jelena; Bilalli, Astrit; Musliu, Milaim; Rey, Isabel (Zootaxa, 2022)
The morphology of all postembryonic stages (larva, pupa, male, and female) of Rhyacophila macedonica Karaouzas, Valladolid, & Ibrahimi n. sp. from Greece, Republic of North Macedonia, Kosovo and Serbia was examined. Morphological data were supplemented by a molecular analysis of the mitochondrial cytochrome C oxidase subunit I (COI) and compared with samples of the nominate species Rhyacophila fasciata Hagen 1859, as well as with other species and subspecies in this group: Rhyacophila septentrionis McLachlan 1865, Rhyacophila denticulata McLachlan 1879, Rhyacophila sociata Navás 1916, Rhyacophila kykladica Malicky & Sipahiler 1993, Rhyacophila fasciata delici Kucinic & Valladolid 2020, and Rhyacophila fasciata viteceki Valladolid & Kucinic 2020. Our results revealed morphological differences between the nominate species and R. macedonica, as well as genetic differences among the taxa in the Rhyacophila fasciata Group, so we propose R. macedonica as a new species of the Group. Based on the new molecular data, we also elevate R. f. delici to the status of a distinct species, R. delici (status promotus).